A visual walkthrough of robotic partial mesorectal excision using the Versius surgical system - Amro Mureb (Intelligent Surgery)
Study objective: To demonstrate a step-by-step surgical technique for partial mesorectal excision using the Versius robotic platform. Design: Stepwise demonstration with narrated video footage. Setting: Our patient is a 62-year-old male with locally advanced rectal cancer involving the middle rectum. The radiological staging was T3N2M0. The multidisciplinary team's recommendation was to give total neoadjuvant chemoradiotherapy (TNT). Post-TNT magnetic resonance image (MRI) showed significant tumour regression and flexible sigmoidoscopy showed stricture around 11 cm from the anal verge. The patient had an uneventful postoperative course and was discharged on postoperative day 3. Final histopathology staging showed a complete response, ypT0N0. Interventions: The required distal margin in partial mesorectal excision (PME) is controversial. Several publications have shown that partial excision of the mesorectum, also called tumour-specific mesorectal excision (TSME), with the division of mesorectum 5 cm below the tumour could be a reasonable approach although total mesorectal excision (TME) is still considered the gold standard for all rectal cancer in many studies. A recent systematic review on distal mesorectal spread and PME showed that for partial mesorectal excision, substantial overtreatment is present if a distal margin of more than 5 cm is routinely utilized; in addition, PME has good oncological results and leads to the best-fitted functional results possible for the patient's condition.1,2 Regarding the morbidity and oncological outcomes after PME, Kanso et al. showed that PME can be performed safely, with a low risk of definitive stoma and local recurrence and the survival rate that was observed, indicates that the prognosis is not altered compared with TME in the treatment of upper and some middle rectal tumour.3 Another study evaluating the oncological outcomes of PME in patients with upper and middle rectal cancer showed that PME and shorter resection margins do not jeopardize the oncological outcomes.4 Robotic colorectal surgery has gained popularity in the last few years as it overcomes most of the limitations of conventional laparoscopic surgery, especially when working in a confined, narrow pelvis. The robotic platform uses multiple technologies like 3-D and stable, precise vision, tremor filtration, and a wide range of instrument tip movement. All these features help the colorectal surgeon complete the rectal surgery more safely and effectively, and like any surgical procedure, standardization of the technique can lead to a shorter learning curve and better outcomes. In this video, we demonstrated a step-by-step approach to tumour-specific mesorectal excision operation using the Versius robotic system platform, starting the mesorectal dissection posteriorly along the plane between the mesorectum and presacral fascia; this dissection should continue distally until reaching at least 5 cm beyond the lower edge of the tumour level which is localised intraoperatively using a rigid sigmoidoscope. Then, the mesorectum is dissected circumferentially starting from the right side, anteriorly and ending the dissection over the left side of the mesorectum. Depending on the location and extent of the tumour, the appropriate level for mesorectal division is determined and partial mesorectal transection is performed starting anteriorly in a counter clockwise pattern. Taking advantage of the high magnification and 3-D vision provided by the robotic platform, all the mesorectal blood vessels are well controlled with good haemostasis using the monopolar scissors and the bipolar Maryland diathermy. Conclusion: The utilization of robotic-assisted partial mesorectal excision represents a major advancement in the management of upper and some middle rectal cancer. Through improved dexterity, precision, and visualization, the robotic platform offers surgeons a valuable tool to navigate difficult pelvic anatomy while maintaining good oncological results and optimizing functional outcomes in PME procedures.